Extracting the Contingency Curve of Fuel Cost-Pollution the Issue of Environmental Economic Burden Distribution - KOSHTEH, MH Karim (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).16, 2018)
In recent decades, SO 2 , CO 2 and NOx emissions from fossil fuels have caused significant social costs. Considering the cost of environmental pollution combined with the cost of exploitation in the distribution of loads in many studies shows the important role of social spending in economic estimates. Minimizing the cost of exploitation along with the cost of emissions in order to meet the demand under the applicable constraints of the power systems known as the modeling of the problem of economic- environmental distribution is load EED (Environmental Economic Dispatch). In this research, the EED problem modeling is optimized by Lagrange’s analytical method based on weight coefficients for the six- generation system. The relationship between EER (Emission Reduction Rate) emission reduction index and fuel cost reduction coefficient is determined and, finally, the extraction of the fuel- pollutant- cost indifference curve is described. Sensitivity analysis has been carried out to achieve the final point of operation of the system, the fuel cost reduction coefficient and the cost- dependency curve of fuel- polluting units. The results are based on these principles: The higher the weight loss factor is the greater the cost of fuel. The cost of operating the system is lower and the cost of emissions is higher. In this case, the problem of the economic distribution of burden or ED (Economic Dispatch) and the minimization of the cost of fuel is the object of the problem. The lower the weight loss factor for fuel costs. The cost of operating the system is higher and the cost of pollution is reduced. In this case, minimizing the cost of emissions is the goal of the problem. The combination of modeling results with indifference curves makes the final point of the system operator clear as the optimal answer to the problem. Utilizing the point of the final operation of the system as the answer to the problem, considering the importance of each goal and how cost and pollution changes are compared to each other.